Cervical sagittal alignment in patients with dropped head syndrome. (12th February 2021) - Qian, Weiqing; Endo, Kenji; Aihara, Takato; Sawaji, Yasunobu; Suzuki, Hidekazu; Matsuoka, Yuji; Takamatsu, Taichiro; Murata, Kazuma; Yamamoto, Kengo
Background: Dropped head syndrome (DHS) can be divided into two types, the positive sagittal vertical axis (SVA) type and the negative SVA type. However, the cervical sagittal alignment of DHS including global sagittal spinal alignment and the typical cervical alignment of the types of DHS is still unclear. The purpose of this study was to clarify the character of cervical sagittal alignment of DHS and analyze the relationship between cervical sagittal alignment and global sagittal spinal alignment. Methods: The subjects were 35 DHS patients (10 men, 25 women, mean 71.1 years old). They were divided into two groups: negative DHS (N-DHS group, SVA < 0 mm) and positive DHS group (P-DHS group, SVA ≥ 0 mm). As control, 28 age-matched cervical spondylosis patients (CS, 21 men, 7 women, mean 67.4 years old) were analyzed. The following parameters were measured on lateral global-spine standing radiographs: cervical SVA (C2-C7SVA), O-C2A (O-C2 angle), C2 slope (C2S), C2-7A (C2-7 angle), T1 slope (T1S) and C7SVA. Results: The results of measurements of each of the averaged sagittal alignment parameters were (CS, P-DHS, N-DHS): C2-7SVA(26.2 mm, 47.3 mm, 44.5 mm), O-C2 angle (35.0°, 37.1°, 39.3°), C2S (16.5°, 31.4°, 33.8°), C2-7A (9.3°, 9.9°, −16.6°), T1S (22.9°, 39.7°, 25.7°), C7SVA (35.3 mm, 51.0 mm, −43.1 mm). C2-C7SVA and C2S were significantly larger in both types of DHS compared to CS. Comparing P-DHS with N-DHS, C2-C7A and T1S were significantly smaller in N-DHS. Conclusions: O-C2A did not differ significantly among CS, P-DHS and N-DHS. In DHS patients, C2-7SVA and C2S were significantly larger than those of CS regardless of the type of DHS. The typical cervical sagittal alignment of DHS was different between P-DHS and N-DHS. In P-DHS, C2-7A and T1S were larger than those in N-DHS and the imbalance of thoraco-lumbar alignment should be noted.